Fundamental Understanding of Magnetic Reconnection via Spiral CT Scan. I. Density, Temperature, Pressure, and Method Validation - H. S. Fu; Z. Wang; J. B. Cao (The Astrophysical Journal)
For the first time, we reveal the distribution of plasma density, electron temperature, thermal pressure, and total pressure around a reconnection X-line, by using the spiral CT scan technique, which is a novel technique analogous to that in the hospital. This X-line was detected by the Magnetospheric Multiscale spacecraft and has been widely believed to host a non-guide-field reconnection in previous studies. With the help of such an advanced technique, we find that (1) the plasma density is low on the magnetosphere side but high on the magnetosheath side; (2) the electron temperature is high on the magnetosphere side but low on the magnetosheath side; (3) the thermal pressure is high near the current sheet but low away from the current sheet; (4) the total pressure in the inflow region is higher than near the current sheet. Among these findings, the first three agree with classical theories, hence validating our novel scan technique; the last one implicates that antiparallel magnetic field lines were being pushed together and the reconnection process was ongoing.